Synthesis of 4,4'-Methylene bis o-Toluidine Based Bisazo Reactive Dyse and Their application - Patel, R.B.; Patel, Nilesh; patel, S.K.; Patel, K.C. (Asian Journal of Chemistry, 2010)
Various bisazo reactive dyes have been prepared by coupling diazotised 4,4'-methylene bis o-toluidine with various o-toluidino cyanurated coupling components such as H-acid, J-acid, K-acid, tobias acid, N-phenyl-J-acid, N-methyl-J-acid, solfo-tobias acid, T-acid and Bronner acid and their dyeing performance as reactive dyes has been assessed on wool, silk and viscose rayon.